2021
DOI: 10.3390/nu14010086
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vitamin D3 Supplementation and Resistance Training on 25-Hydroxyvitamin D Status and Functional Performance of Older Adults: A Randomized Placebo-Controlled Trial

Abstract: Vitamin D status is associated with muscle strength and performance in older adults. To examine the additive effects of vitamin D3 supplementation during resistance training, 100 seniors (65–85 years) participated in a 16-week intervention. Besides a daily dose of 400 mg of calcium, participants received either 800 IU vitamin D3 per day (VDD), 50,000 IU vitamin D3 per month (VDM) or nothing (CON). After the initial loading phase of four weeks, all groups started a 10-week resistance training program. Assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 61 publications
1
28
0
Order By: Relevance
“…Detailed seasonal information was provided in Aschauer's study (from mid-February to mid-July) [78], Sun's study (from March to July) [77], and Agergaard's study (from November to December) [79]. We found a clear seasonal trend in mean serum 25(OH)D concentrations, suggesting that the change in 25(OH)D concentrations induced by resistance training may have been caused by large seasonal fluctuations [77,78].…”
Section: Human Studiesmentioning
confidence: 69%
See 2 more Smart Citations
“…Detailed seasonal information was provided in Aschauer's study (from mid-February to mid-July) [78], Sun's study (from March to July) [77], and Agergaard's study (from November to December) [79]. We found a clear seasonal trend in mean serum 25(OH)D concentrations, suggesting that the change in 25(OH)D concentrations induced by resistance training may have been caused by large seasonal fluctuations [77,78].…”
Section: Human Studiesmentioning
confidence: 69%
“…Resistance exercise training significantly increased circulating 25(OH)D levels in vitamin D-deficient post-stroke hemiplegia patients [75] and healthy participants [76]. Conversely, resistance exercise training had no effect on 25(OH)D lev-els in healthy vitamin D-deficient young men [77] and older adults without vitamin D supplementation [78]. However, Agergaard et al found that resistance exercise training significantly reduced serum 25(OH)D levels in young and elderly participants without vitamin D supplementation [79].…”
Section: Human Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Sarcopenia and impaired muscle strength have also been related to vitamin D deficiency [ 77 , 78 ]. On the other hand, vitamin D supplementation has been associated with improved aerobic and anaerobic capacity of healthy subjects [ 79 ], even though other studies did not observe improvements in muscular performance [ 80 , 81 ], suggesting that the impact of vitamin D supplements on exercise or sport performance has yet to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are also similar to those of Savolainen et al described earlier [ 13 ] and another recent study by Molmen et al [ 67 ], who reported that vitamin D supplementation had no effect on resistance training-induced changes in muscle strength, mass and performance in older adults. Other recent exercise and vitamin D trials have also reported no additive effects of vitamin D supplementation on aerobic capacity when combined with aerobic [ 68 ] or resistance exercise [ 69 ].…”
Section: Discussionmentioning
confidence: 99%